Lending a hand to storytelling: Gesture's effects on narrative comprehension moderated by task difficulty and cognitive ability. Issue 10 (October 2021) - McKern, Nicola; Dargue, Nicole; Sweller, Naomi; Sekine, Kazuki; Austin, Elizabeth
Compelling evidence suggests observing iconic gestures benefits learning. While emerging evidence suggests typical iconic gestures benefit comprehension to a greater extent than atypical iconic gestures, it is unclear precisely when and for whom these gestures will be most helpful. The current study investigated factors that may moderate when and for whom gesture benefits narrative comprehension most, including the type of gesture, task difficulty, and individual differences in cognitive ability. Participants were shown a video narrative in which they observed either typical gestures (commonly produced gestures, highly semantically related to accompanying speech), atypical gestures (gestures that are seldom produced), or no gestures. The video narrative was either viewed with interference (background noise to increase task difficulty) or no interference (no background noise). To determine whether the effects of gesture observation and externally imposed task difficulty on narrative comprehension further depend on an individual's cognitive abilities, participants completed four measures of cognitive abilities (immediate and delayed non-verbal memory, attention, and intellectual ability). Observing typical gestures significantly benefitted narrative comprehension compared with atypical and no gestures combined, which did not differ significantly. Participants with below average and average levels of delayed non-verbal memory benefitted more from typical gestures than atypical or no gestures compared with those with an above average level of delayed non-verbal memory. However, this interaction was only significant when the task was difficult (i.e., with interference) but not when the task was simple (i.e., no interference). This finding suggests that the type of iconic gesture observed may affect gesture's beneficial effect on narrative comprehension, and that such gestures may be more beneficial in difficult tasks, but only for certain individuals.